Preparation and Characterization of Hydrogenated Castor Oil‐Based Coating Wax. Issue 4 (19th February 2018) - Huyan, Zongyao; Ding, Shaoxuan; Yu, Xiuzhu; Liu, Xiaoli
Abstract : A synthesis method is developed from a reaction between hydrogenated castor oil (HCO) and ethylenediamine to prepare a product to coat paperboard. For highest conversion rate, a molar ratio of 1:3 of HCO and ethylenediamine reacted at 130 °C for 2.5 h. Fourier transform infrared (FTIR) spectroscopy and Nuclear magnetic resonance (NMR) confirm the obtained product is a wax combining HCO with two amide groups. The melting point of the diamide wax is 130 °C. The hardness of the wax is harder than that of other waxes (over eight times to beeswax and over four times to paraffin wax) except carnauba wax. In addition, the cohesiveness of the HCO diamide wax is slightly poorer than that of others. In coating paperboard application, the performance of diamide wax in compression force of all treatments is similar to that of carnauba wax and better than that of other waxes although soaking allows paperboard coated with the wax to have wax loss and compression force loss. The results show that the HCO wax with diamide group can be a good coating material on paperboard. Practical Applications : The synthesis method is used to prepare a good coating material. The HCO material is confirmed to be diamide wax after structure confirmation by FTIR and NMR. This diamide wax shows good physical properties and plays well in coating paperboard for its high adhesive rate and good compression force with or without soaking or heating. It also shows a good adhesive ability while heating. The application test presents that the HCO‐based diamide wax is good substitute for other wax such as carnauba wax for coating. A synthesis method by the reaction between hydrogenated castor oil (HCO) and ethylenediamine is used to prepare a coating material. After conducting several attempts, a molar ratio of 1:3 of HCO and ethylenediamine reacted at 130 °C for 2.5 h to acquire the final product. The HCO product is confirmed to be diamide wax after structure confirmation by Fourier transform infrared spectroscopy and nuclear magnetic resonance. The properties of diamide wax are evaluated by texture analyzer and differential scanning calorimetry. By evaluating the coating ability on paperboard, results show that the diamide wax is a good coating material. Abstract : A synthesis method by the reaction between hydrogenated castor oil (HCO) and ethylenediamine is used to prepare a coating material. After conducting several attempts, a molar ratio of 1:3 of HCO and ethylenediamine reacted at 130 °C for 2.5 h to acquire the final product. The HCO product is confirmed to be diamide wax after structure confirmation by Fourier transform infrared spectroscopy and nuclear magnetic resonance. The properties of diamide wax are evaluated by texture analyzer and differential scanning calorimetry. By evaluating the coating ability on paperboard, results show that the diamide wax is a good coating material.